Akta Hibah dari PPAT Sementara Camat yang Dibuat Tanpa Kehadiran Para Pihak (Studi Kasus Putusan Mahkamah Agung Republik Indonesia Nomor 1565 K/PDT/2023) - Indriani, Ferica; Lukman, Arsin (UNES Law Review, 2024)
Grant deed is an authentic deed made by Conveyancer which contains an agreement whereby the grantor, while still living, grants assets voluntarily and irrevocably for the benefit of the grantee who accepts such. Regarding the grant deed made by Temporary Conveyancer (Subdistrict Head), such deed should comply the formal and material terms of an authentic deed. One of the formal terms is the deed must be made before the parties and at least 2 witnesses. However, in practice, Temporary Conveyancer (Subdistrict Head) made the grant deed without the presence of parties and witnesses. This research analyzes the legal consequences of a grant deed made without the presence of the parties and witnesses as well as the responsibilities of the Temporary Conveyancer (Subdistrict Head) regarding the grant deed. This research was prepared using doctrinal research methods. The legal consequence of a Grant Deed made without the presence of the parties and witnesses is the deed loses its authenticity and causes the Grant Deed to be null and void. The Grant Deed made by Temporary Conveyancer (Subdistrict Head) without the presence of the parties and witnesses in accordance with statutory regulations, may be subject to administrative sanctions, civil sanctions and criminal sanctions.